Modeling of supersaturated dissolution data - Valsami, G.; Dokoumetzidis, A.; Macheras, P. (INTERNATIONAL JOURNAL OF PHARMACEUTICS, 1999)
A recursion equation which relies on the population growth model of dissolution is used for the analysis of supersaturated dissolution data. The concentration-time data of dissolution experiments are initially transformed to fractions of dose dissolved-generations by adopting an appropriate time interval as the time step of the recursion equation. A computer program is used to derive estimates for the maximum fraction of dose dissolved and the fraction of dose remaining in solution at steady state. Good fittings were observed when this equation was applied to phenytoin and nifedipine supersaturated dissolution data obtained from literature. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: difference equation; Dissolution; modeling; population growth model; Supersaturation